Agama Dan Negara Dalam â€œKritik Nalar Arabâ€ Al-Jabiri - Ahmad Ali Riyadi (Millah: Journal of Religious Studies, 2003)
The discourse on religion and state relation denote the classical discussion which has no ending up to this present. Many Islamic thinkers have been discussing such issues for along time ago until today. This paper tries to discuss one of Islamic contemporary thinker, namely, Abed al-Jabiriâ€™s thought on such theme. Actually, an Islamic state for al-Jabiri did not exist and even never happen. The changing of daâ€™wah from the uninstituted pattern to the instituted one called Islamic state constituted the ijtihad caused two aspects: first, the Arab society condition in that time was the tribe who like to fight. Secondly, the need of power to support the survival of new independence society. According to al-Jabiri, Islamic state was not the fact but it was the Islamic moral practiced individually and institutionally. The state in Islam is constitutional system.